Acute care and secondary prevention of stroke with newly detected versus known atrial fibrillation. (12th April 2022) - Wang, Ruihao; Macha, Kosmas; Haupenthal, David; Gaßmann, Luise; Siedler, Gabriela; Stoll, Svenja; Fröhlich, Kilian; Koehn, Julia; Schwab, Stefan; Kallmünzer, Bernd
Abstract: Background and purpose: Atrial fibrillation (AF) in stroke patients can be classified as either "known AF" (KAF), defined as AF confirmed before stroke onset, or "AF detected after stroke" (AFDAS), defined as AF diagnosed after stroke onset. While KAF is considered primarily cardiogenic, AFDAS includes patients with stroke‐triggered neurogenic arrhythmias. This study aimed to investigate the clinical course of stroke, functional outcomes and the value of oral anticoagulation (OAC) for secondary prevention according to AF subtype. Methods: Acute ischemic stroke patients were consecutively enrolled and AF was classified as AFDAS or KAF. Stroke severity was assessed using the National Institutes of Health Stroke Scale (NIHSS) and 3‐month functional outcomes were measured on the modified Rankin scale. Inverse probability weighting was applied to adjust for baseline confounders in patients with AFDAS and KAF. Multivariate logistic regression models were calculated to investigate the value of OAC for secondary prevention. Results: A total of 822 stroke patients with AF were included, of whom 234 patients (28.5%) had AFDAS. AFDAS patients had a lower prevalence of coronary artery disease, heart failure, and sustained AF, but higher rates of large vessel occlusion compared to KAF patients. NIHSS scores were lower in patients on pre‐stroke anticoagulation. OAC for secondary prevention was associated with favorable 3‐month functional outcome (odds ratio 7.60, 95% confidence interval 3.42–16.88) independently of AF subtype. The rate of stroke recurrence did not differ significantly. Conclusions: Clinical characteristics suggest that AFDAS might comprise a distinct pathophysiological and clinical entity among stroke patients with AF. The benefit of anticoagulation for secondary prevention was not affected by AF subtype. Abstract : Among 822 stroke patients with atrial fibrillation (AF), 28.5% had AF detected after stroke (AFDAS). Compared to known AF, AFDAS patients had lower prevalence of coronary artery disease, heart failure and sustained AF, but higher rates of large‐vessel occlusion. These results suggest that AFDAS comprises a distinct pathophysiologic and clinical entity. The functional outcomes, the rates of stroke recurrence and the benefit of anticoagulation for secondary prevention were not affected by AF subtype.